Income, wealth, and the maximum principle - Weitzman, Martin L., 1942- (Harvard University Press, 2003)
Annotation This compact and original exposition of optimal control theory and applications is designed for graduate and advanced undergraduate students in economics. It presents a new elementary yet rigorous proof of the maximum principle and a new way of applying the principle that will enable students to solve any one-dimensional problem routinely. Its unified framework illuminates many famous economic examples and models. This work also emphasizes the connection between optimal control theory and the classical themes of capital theory. It offers a fresh approach to fundamental questions such as: What is income? How should it be measured? What is its relation to wealth?The book will be valuable to students who want to formulate and solve dynamic allocation problems. It will also be of interest to any economist who wants to understand results of the latest research on the relationship between comprehensive income accounting and wealth or welfare.